Multifactorial monitoring of training load in elite rugby sevens players: cortisol/cortisone ratio as a valid tool of training load monitoring - Bouaziz, T; Makni, E; Passelergue, P; Tabka, Z; Lac, G; Moalla, W; Chamari, K; Elloumi, M (Biology of Sport, 2016)
The effectiveness of selected physiological and perceptual measures for monitoring training load and fatigue was studied in 16 male elite rugby sevens players during a 6-week intense training block (IT) and 2-week tapering (TAP). Daily training load (TL) and strain (TS) as well as weekly total score of fatigue (TSF) were quantified respectively by the session-rating of perceived exertion (RPE) method and an 8-item questionnaire. Also, testing was performed and 24 h urinary cortisol (C), cortisone (Cn), adrenaline (A) and noradrenalin (NA) excretion was measured before (T0) and after the IT (T1) and after the TAP (T2). The TL, TS and TSF increased during the IT and decreased during the TAP, in conjunction with a significant drop and improvement, respectively, of performance standards during the two periods. At T1, C and Cn levels increased while A and NA levels decreased, resulting in a higher C/Cn ratio and lower A/NA ratio, respectively. At T2, both C/Cn and A/NA returned to baseline values. The changes in C/Cn ratio, after the 6-week IT, were more closely related to mean TL, TS and TSF (r=0.75-0.76 vs. r=0.48-0.58, p<0.01) and to changes in the majority of performance measures than to A/NA ratio. Only the changes in C/Cn ratio after the 2-week TAP were related to mean TL, TS and TSF (r=0.61-0.68, p<0.01). The changes in hormone levels, training strain and performance standards reflected the physical and mental stressors of training, with complete recovery, as indicated by physiological homeostasis, achieved after an appropriate tapering period.